PROFILE OF '˜ORIGINAL ARTICLES' PUBLISHED IN 2016 BY THE JOURNAL OF AYUB MEDICAL COLLEGE, PAKISTAN - Shaikh, Masood Ali (Journal of Ayub Medical College Abbottabad, 2018)
Journal of Ayub Medical College (JAMC) is the only Medline indexed biomedical journal of Pakistan that is edited and published by a medical college. Assessing the trends of study designs employed, statistical methods used, and statistical analysis software used in the articles of medical journals help understand the sophistication of research published. The objectives of this descriptive study were to assess all original articles published by JAMC in the year 2016. JAMC published 147 original articles in the year 2016. The most commonly used study design was cross-sectional studies, with 64 (43.5%) articles reporting its use. Statistical tests involving bivariate analysis were most common and reported by 73 (49.6%) articles. Use of SPSS software was reported by 109 (74.1%) of articles. Most 138 (93.9%) of the original articles published were based on studies conducted in Pakistan. The number and sophistication of analysis reported in JAMC increased from year 2014 to 2016. Keywords: Statistics Software; Pakistan Publication; JAMC; Research Journal